Application of Plant Growth Promoting Rhizobacteria to Improve Soil Chemical and Biological Properties and Its Effect on Growth, Physiology and Yield of Okra (Abelmoschus esculentus L) - Zakiah Mustapha,; Nik Nurnaeimah Nik Mohamad Nasir,; Mohd Khairi Che Lah,; Norhayati Ngah,; Khamsah Suryati Mohd,; Radziah Othman,; Hafizan Juahir, (Tropical Life Sciences Research, 2025)
The use of Plant Growth-Promoting Rhizobacteria (PGPR) as a biofertiliser was proven to be successful in the optimisation of plant growth and yield. A field experiment was conducted to evaluate the effectiveness of the PGPR on okra growth, physiology, yield and soil physicochemical properties. The okra was planted and fertilised with organic material (goat dung) at 500 g/plant, NPK fertiliser at 100 g/plant (T1) and 70 g/plant for T2, T3, T4 and T5, respectively. The BRIS soil isolated PGPR, namely UA 1 (Paraburkholderia unamae), UA 6 (Bacillus amyloliquefaciens) and UAA 2 (Enterobacter asburiae) propagated in 6% molasses medium were inoculated with the amount of 40 mL for single strain treatment (T2–T4) and 15 mL of each bacterial inoculum for mixed strains treatment (T5). Results showed that inoculation with PGPR in single or mixed strains has significantly decreased the use of 30% NPK fertiliser and promoted okra growth, physiology, yield and soil chemical properties and bacterial count. Mixed strains (T5) have significantly shown the highest performance with increments of 27.85% of leaf number, 28.56% of okra number, 27.90% of yield per plant and 25.83% of plant total dry biomass. The plant net photosynthesis treated with mixed strains also recorded a 5.27% increment with 26.96% of nitrogen content and 22.79% bacteria count in the soil. The findings of this study suggested that the BRIS soil PGPR inoculants may reduce the amount of chemical fertiliser and have a significant potential to be used as biofertiliser in sustainable agriculture to increase plant growth and yield and soil fertility.